Short communication: Plasma levels of vitamin D in HIV patients initiating antiretroviral therapy do not predict immune restoration disease associated with mycobacterium tuberculosis - Price, Patricia; Haddow, L.; Affandi, J.; Agarwal, U.; Easterbrook, P.; Elliott, J.; French, M.; Kumar, M.; Moosa, M.; Oliver, B.; Singh, S.; Sola, M.; et al. (2012)
Immune restoration disease associated with Mycobacterium tuberculosis (TB IRD) is clinically important among HIV patients commencing antiretroviral therapy in countries where tuberculosis is endemic. Vitamin D affects dendritic cell and T cell function and the antimicrobial activity of monocytes. Plasma levels of vitamin D and polymorphisms in the vitamin D receptor may affect tuberculosis, and HIV infection associates with vitamin D deficiency. Here we assess whether plasma vitamin D levels may predict TB IRD. Samples were available from prospective studies of TB IRD in Cambodia (26 cases), India (19 cases), and South Africa (29 cases). IRD cases and controls from each site were similar in age and baseline CD4+ T cell count. Plasma samples were assessed using 25(OH) vitamin D immunoassay plates. DNA samples were available from a subset of patients and were genotyped for the VDR FokI (F/f) [C/T, rs10735810] SNP. When data from each cohort were pooled to assess ethnic/geographic differences, 25(OH)D levels were higher in Cambodian than Indian or South African patients (p<0.0001) and higher in South African than Indian patients (p<0.0001). TB IRD was not associated with differences in levels of 25(OH)D in any cohort (p=0.36-0.82), irrespective of the patients' prior TB diagnoses/treatment. Carriage of the minor allele of VDR FokI (F/f) was marginally associated with TB IRD in Indian patients (p=0.06) with no association in Cambodians. Neither plasma levels of vitamin D nor the vitamin D allele will usefully predict TB IRD in diverse populations from TB endemic regions. © 2012, Mary Ann Liebert, Inc.